2020
DOI: 10.1002/smll.201905959
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of DNA Origami Nanostructures

Abstract: Although DNA origami nanostructures have found their way into numerous fields of fundamental and applied research, they often suffer from rather limited stability when subjected to environments that differ from the employed assembly conditions, that is, suspended in Mg2+‐containing buffer at moderate temperatures. Here, means for efficient cryopreservation of 2D and 3D DNA origami nanostructures and, in particular, the effect of repeated freezing and thawing cycles are investigated. It is found that, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 45 publications
3
34
0
Order By: Relevance
“…However, it can also be stable at temperatures >85 °C with photo-cross-linking-assisted thermal stability 80 . DNA origami can also be lyophilized and stored under freezing conditions 265 . For the cationic strength, many approaches have been reported to protect DNA origami from destabilization, especially at low Mg 2+ concentrations or without Mg 2+ (refS 70,71 ).…”
Section: Reproducibility and Data Depositionmentioning
confidence: 99%
“…However, it can also be stable at temperatures >85 °C with photo-cross-linking-assisted thermal stability 80 . DNA origami can also be lyophilized and stored under freezing conditions 265 . For the cationic strength, many approaches have been reported to protect DNA origami from destabilization, especially at low Mg 2+ concentrations or without Mg 2+ (refS 70,71 ).…”
Section: Reproducibility and Data Depositionmentioning
confidence: 99%
“…[147] In summary, we firmly believe that DNA nanotechnology has the potential to produce formidable and powerful weapons for the fight against infectious diseases. Many of the basic aspects of DNA nanostructures that have been uncovered in the past decade, for instance regarding stability, [149] cellular uptake, [150] and immune response, [136] but also with respect to mass production [151] and storage, [152] will without doubt be of tremendous value also in this endeavor. Due to the great variety of infectious diseases and the high diversity of viral, bacterial, fungal, and parasitic pathogens, however, the road ahead will also present many challenges that have to be overcome to establish biomedical DNA nanotechnology also in the area of infectious disease diagnostics and therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Considering the real application in detecting and curing diseases, the storage, scalability and cost become highly pertinent question. Some studies demonstrated that lyophilization and cryostorage could keep origami nanostructure intact for up to several years [102][103][104]. In 2017, Dietz et al [105] realized scalable biotechnological production of single stranded DNA with arbitrary length and sequence, which would remove a key obstacle in the way of application of origami-based biosensor.…”
Section: Discussionmentioning
confidence: 99%